Identifikasi dan Penetapan Kadar Senyawa Saponin Ekstrak Etanol Bunga Senggani (Melastoma malabathricum L) Metode Gravimetri - Yuska Noviyanty; Hepiyansori Hepiyansori; Berliana Rosita Dewi (Denta Journal Kedokteran Gigi, 2020)
Traditional medicine is an ancestral cultural heritage derived from natural materials and to this day continue to be used by the general public. One of the plants that can be used as a traditional medicine is a plant Senggani (Melastoma malabathricum L). The purpose of this study was to determine the saponins contained from flower extracts Senggani (Melastoma malabathricum L) and percent saponin levels of Senggani flower extract (Melastoma malabathricum L). Extraction is done by maceration using ethanol 96% for 5 days. Extraction obtained is then concentrated by means of a rotary evaporator. The results were qualitative identification of the foam test and color test and quantitative assay with gravimetric method.Based on research conducted Senggani ethanol extracts of flowers (Melastoma malabathricum L) contains saponins types of triterpenoids seen from the ring in maroon and obtained the average level of interest saponin Senggani (Melastoma malabathricum L) is 11.46%.